Cardiovascular Autonomic Dysfunction in Type-2 Diabetes patients with Microalbuminuria in a Tertiary Level Hospital - Miah, Md Rubel; Rahman, Md Saidur; Biswas, Sarmistha; Banik, Gobinda Chandra; Chowdhury, Md Faizul Islam (Journal of Medicine, 2018)
Background: Cardiovascular autonomic dysfunction is a serious complication of diabetes mellitus (DM) and is independently associated with microalbuminuria in patients with type-2 DM. This study was conducted to determine the prevalence of cardiovascular autonomic dysfunction in type-2 diabetes patients with microalbuminuria. Materials & Methods: This descriptive type of observational study was done in the department of Medicine, Dhaka Medical College Hospital from August 2015 to January 2016. Results: A total of 50 patients was included in the study with male predominance (M:F ratio 2. 22:1). Peak age was between 40-60 years and majority of patients (32%) was between 41-50 years and mean duration of DM was more than 12 years. Out of 50 patients, 19 (38%) patients had mild microalbuminuria; 24 (48%) patients had moderate microalbuminuria and 7 (14%) patients had severe microalbuminuria. Common symptoms were lethargy, anorexia, nausea, vomiting, dizziness and bladder symptoms. Cardiac autonomic neuropathy (CAN) was found in 80% cases. Parasympathetic dysfunction was observed in 40 (80%) cases and sympathetic dysfunction was observed in 43 (86%) cases. Conclusion: As significant number of DM patients (80%) develop CAN, so cardiovascular autonomic function tests should be monitored to address major potential cardiovascular complications even in asymptomatic patients, especially among those with microalbuminuria. J MEDICINE JUL 2018; 19 (2) : 104-109